Replication study of MATR3 in familial and sporadic amyotrophic lateral sclerosis - Leblond, Claire S.; Gan-Or, Ziv; Spiegelman, Dan; Laurent, Sandra B.; Szuto, Anna; Hodgkinson, Alan; Dionne-Laporte, Alexandre; Provencher, Pierre; de Carvalho, Mamede; Orrù, Sandro; Brunet, Denis; Bouchard, Jean-Pierre; et al. (Neurobiology of aging, 2016)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disorder characterized by an extensive loss of motor neurons in the primary motor cortex, brainstem, and spinal cord. Genetic studies report a high heritability of ALS. Recently, whole-exome sequencing analysis of familial ALS (FALS) patients allowed the identification of missense variations within the MATR3 gene. MATR3 was previously associated to distal myopathy 2 and encodes for a nuclear matrix and DNA/RNA binding protein that has been shown to interact with TDP43 in an RNA-dependent manner. Here, we assessed the MATR3 mutation frequency in French-Canadian ALS and control individuals (nFALS = 83, sporadic ALS [nSALS] = 164, and ncontrols = 162) and showed that MATR3 mutations were found in 0%, 1.8%, and 0% of FALS, SALS, and controls, respectively. Interestingly, among the mutations identified in SALS, the splicing mutation c.48+1G>T was found to result in the insertion of 24 amino acids in MATR3 protein. These findings further support the role of MATR3 in ALS, and more studies are needed to shed more light on MATR3 proteinopathy.